Development of Digital Comic Strip Media in Indonesian Language Learning to Enhance Critical Thinking Skills - Abdullah, Annisa Thalia; Laily , Idah Faridah; Masnun , Moh. (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This research is motivated by initial findings from interviews with teachers and students. The aims of this study are as follows: 1) to explore the design of developing digital-based comic strip media, 2) to assess the feasibility of digital-based comic strip media and 3) to evaluate the effectiveness of digital-based comic strip media. The method used is Research and Development (RnD). There are five stages of development in the RnD method based on the ADDIE model: analysis, design, development, implementation and evaluation. The results of the validation tests showed that the digital-based comic strip media received an 80% rating in the media expert validation test, categorizing it as feasible. In the language expert validation test, it received a 94% rating, categorizing it as very feasible and in the material expert validation test, it also received a 94% rating, categorizing it as very feasible. Furthermore, the digital-based comic strip media in indonesian language learning has proven effective in improving students' critical thinking skills, as demonstrated by the N-Gain test, which yielded an average score of 0.87 and an average percentage of 87.48. Therefore, digital-based comic strip media is deemed feasible for implementation and effective in enhancing students' critical thinking skills.